Ceramic coating film for in-situ growth on surface of steel through micro-arc oxidation and preparation method of ceramic coating film
By using sodium aluminate and sodium hexametaphosphate electrolyte combined with microarc oxidation treatment on the surface of medium carbon steel and mold steel, the in-situ growth of the ceramic coating is achieved, solving the problem of insufficient coating thickness and bonding strength in the prior art, and achieving a ceramic coating with high hardness and corrosion resistance.
Patent Information
- Application Number
- CN202510043146.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-08
AI Technical Summary
It is difficult for the prior art to prepare ceramic coatings with higher thickness directly through microarc oxidation technology on the surfaces of medium carbon steel and mold steel, and the existing coatings are prone to fall off and crack during long-term use, and have a low bonding strength.
The electrolyte containing sodium aluminate and sodium hexametaphosphate is synergistically used to achieve microarc oxidation treatment. By controlling electronic control parameters such as voltage, current density and frequency, the in-situ growth of the ceramic coating can be achieved, with a thickness of up to 131μm and a hardness of up to 650HV or more.
A ceramic coating with a thickness of more than 100 μm was prepared on the surface of medium carbon steel and mold steel, which improved the overall performance of the film layer, including hardness, corrosion resistance and photocatalytic characteristics, and avoided the problems of coating shedding and cracking.
Smart Images

Figure CN119776943A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic coating on the surface of steel, in particular to a ceramic coating grown in situ by micro-arc oxidation on the surface of steel and a preparation method thereof, belonging to the technical field of metal surface protection and coating. Background Art
[0002] Steel is an important pillar material and is widely used in various fields. For example, in the field of building structures, it is widely used in steel frame structures, reinforced concrete, large bridges and other structures. In the field of transportation, automobile engines and chassis, train tracks and bodies, ship frames and propulsion systems all require a large amount of steel. In the field of mechanical manufacturing, such as manufacturing tools and machine parts, H13 mold steel is widely used in extrusion molds, die-casting molds, stamping molds, hot forming molds, etc. The service conditions of mold steel are harsh. During the processing, the mold surface is subjected to high-pressure friction of the billet, causing wear. The high processing temperature reduces the hardness and wear resistance of the mold surface, aggravating the wear of the mold. The die-casting mold is in direct contact with the high-temperature aluminum alloy molten metal with relatively active chemical properties, which corrodes the mold surface. Liquid Pb-Bi in the nuclear reactor circulation loop corrodes steel material components such as Q235 and 316 stainless steel. There are some inevitable limitations in the application of steel materials, such as corrosion and rust in an environment containing corrosive media, and friction and wear that seriously reduce the service life of steel materials.
[0003] There are many surface treatment methods for steel materials, such as pickling, mechanical treatment (grinding, polishing, brushing), plating treatment (common plating treatment methods include electroplating, hot dip plating, thermal spraying, etc.), coating treatment (including spraying, rolling, dipping), etc. Surface treatment can significantly improve the corrosion resistance, wear resistance and aesthetics of steel. These surface treatment methods have been widely used in industry, but there are still technical difficulties that restrict their service life. For example, carbon, nitrogen and other diffusion treatments at around 500°C will cause mold deformation; surface coatings such as chrome, nickel, TiN, CrN, TiAlN have poor toughness, and the interface bonding strength between the coating and the mold is low. During long-term use, the coating is prone to fall off and cracking.
[0004] Micro-arc oxidation is a material surface treatment technology developed on the basis of anodizing. Through plasma discharge, a ceramic film mainly composed of metal oxides can be grown in situ on the surface of aluminum, magnesium, titanium, zirconium and their alloys. The film has good wear resistance, corrosion resistance and electrical insulation properties. However, as a non-valve metal, it is difficult to prepare a ceramic coating directly on the surface of steel through micro-arc oxidation technology, especially in the field of medium carbon steel and alloy mold steel, which is rarely reported. Most researchers use a conversion film pre-prepared on the surface of steel, such as a layer of valve metal aluminum or titanium, and then micro-arc oxidation. In the prior art, Lu et al. (Evolution of micro-arc oxidation behaviors of the hot-dipping aluminum coatings on Q235 steel substrate, Appl. Surf. Sci. 257 (2011) 4144-4150) used sodium silicate as an electrolyte and adopted a combination of hot-dip aluminum plating and micro-arc oxidation to prepare a ceramic coating containing aluminum oxide on the surface of Q235 low-carbon steel; Durdu et al. (Korkmaz, Characterization and mechanical properties of the duplex coatings produced on steel by electro-spark deposition and micro-arc oxidation, Surf. Coat. Technol. 236 (2013) 303-308) successfully prepared a coating with high hardness and friction performance on the surface of ST35 steel by first electrodepositing a layer of Ti6Al4V on the surface of ST35 steel and then performing micro-arc oxidation. When this method is used, the metal coating such as aluminum or titanium exists between the steel surface and the prepared ceramic layer, and there are often prominent problems such as poor bonding strength between the coating and the substrate, and insufficient mechanical properties and heat resistance of the coating. So far, some researchers have directly prepared micro-arc oxidation films on the surface of low-carbon steel, such as Q235 carbon steel, and confirmed through various characterization methods that the corrosion resistance and hardness of the film layer are improved compared to the substrate.For example, Wang et al. (Effects of Na2WO4 and Na2SiO3 additives in electrolytes on microstructure and properties of PEO coatings on Q235 carbon steel, J. Alloys Compd. 481 (2009) 725e729) used sodium aluminate and sodium dihydrogen phosphate electrolyte to directly prepare a ceramic film on the surface of Q235 low-carbon steel. Characterization showed that the corrosion resistance of the film was significantly improved compared with that of the substrate. Malinovschi et al. (Iosub, Preparation and characterization of coatings on carbon steel obtained by PEO in silicate / carbonate electrolyte, Surf. Coat. Technol. 296 (2016) 96-103) used a mixed electrolyte of sodium silicate and sodium carbonate to micro-arc oxidation treatment of S235JR low-carbon steel. The research results showed that the hardness and wear resistance of the prepared film material were greatly improved. Cheng et al. (Formation of ceramic coatings on non-valvemetal low carbon steel using micro-arc oxidation technology, Ceram. Int. 50(2024) 23541-23549) directly micro-arc oxidized 20 steel in an electrolyte of sodium aluminate and sodium dihydrogen phosphate. The corrosion current density of the prepared ceramic coating was reduced by one order of magnitude compared with the substrate. Although a certain electrolyte composition, such as sodium aluminate or sodium silicate system, can be used to directly prepare a ceramic film layer on the surface of steel materials, most of them have defects such as thin thickness, which is difficult to exceed 50μm, loose microstructure and uneven coating color. In summary, the current research on steel materials is mostly concentrated in the field of low carbon steel, and there are few similar studies in the fields of medium carbon steel and mold steel. Summary of the invention
[0005] In view of the problems existing in the prior art, the first object of the present invention is to provide a ceramic coating grown in situ by micro-arc oxidation on the surface of steel. The coating is based on the synergistic effect between the electrolyte system and the micro-arc oxidation treatment. While achieving the in-situ growth of a thicker film layer in a short time, the comprehensive performance of the film layer is greatly improved. After testing, the ceramic coating provided by the present invention has a thickness of up to 131 μm and a hardness of up to 650 HV. It has an ultra-low glossiness of only 0.1 at most, and the film layer also has excellent photocatalytic properties. The concentration of methyl orange with a concentration of 5 mg / L can be reduced by more than 80% in 12 hours, and can be used for catalytic oxidation and degradation of organic matter in an aquatic environment.
[0006] The second object of the present invention is to provide a method for in-situ growth of a ceramic coating on a steel surface by micro-arc oxidation. The method can not only greatly improve the growth rate of the ceramic coating, but also achieve quantitative control of the thickness of the ceramic coating by controlling the electrical control parameters during the micro-arc oxidation treatment. Since the method mainly utilizes the electrochemical reaction between the electrolyte and the local high-energy field micro-region on the surface of the steel to grow the ceramic coating, the method does not need to prepare a conversion layer on the surface of the substrate, and can achieve the preparation of a ceramic coating with a thickness of more than 100 μm on the surface of medium-carbon steel with a high carbon content, such as mold steel, in a short time.
[0007] In order to achieve the above technical objectives, the present invention provides a method for in-situ growth of ceramic coating on the surface of steel by micro-arc oxidation, comprising: Step S1, the steel is placed as an anode in an electrolytic cell after being pretreated; Step S2, adding an electrolyte containing sodium aluminate and sodium hexametaphosphate into an electrolytic cell, using the electrolytic cell as a cathode, and performing micro-arc oxidation treatment on the steel; Step S3, cleaning and drying the steel material after micro-arc oxidation, to obtain; The concentration of sodium aluminate in the electrolyte is 7-9 g / L, and the concentration of sodium hexametaphosphate is 1-3 g / L.
[0008] In the electrolyte system provided by the present invention, the key to preparing a ceramic film layer on the surface of steel is that the initially formed AlPO4 and Al(PO3)3 form a passivation layer, which provides stable support for subsequent plasma discharge. The NaAlO2 component in the electrolyte provides a source of metal ions for the passivation layer, and the Na(PO3)6 relative molecular mass is very large. During the initial establishment of a stable electric field on the surface of the film layer, it can be tightly attached to the surface of the material, thereby forming an effective material conversion. Only when the ratio of the two meets the above requirements can a uniform and dense ceramic film layer be formed on the surface of the film layer. When the components or ratios are changed, the surface of the ceramic layer will become rough and uneven, and may fall off in severe cases.
[0009] As a preferred solution, the pretreatment process of the steel material is: after cutting the steel material, grinding, polishing and ultrasonic cleaning are used to remove surface stains and oxide layers.
[0010] As a preferred solution, the electrolyte further contains an auxiliary additive with a concentration of 0-50 g / L.
[0011] As a preferred solution, the electrical control parameters of the micro-arc oxidation treatment are: the positive voltage is 200~750V, the negative voltage is 0~250V, and the current density is 5~50A / dm 2 , frequency is 50~10000Hz, duty cycle is 5~95%, and the ratio of positive and negative pulses is 1:1.
[0012] As a preferred solution, the forward direction adopts at least one of a segmented constant voltage mode, a constant voltage mode and a constant current mode.
[0013] As a preferred solution, the negative direction adopts a constant voltage mode or a constant current mode, and the average current intensity in the negative direction is less than or equal to the average current intensity in the positive direction.
[0014] As a preferred solution, when the forward direction adopts the segmented constant voltage mode, the starting voltage is 200~500V, the number of segments is 5~10, the voltage increment of each segment is 10~50V, the maintenance time of each segment is 1~5min, and the negative direction is not loaded. Further preferably, when the forward direction adopts the segmented constant voltage mode, the starting voltage is 400~500V, the number of segments is 5~8, the voltage increment of each segment is 10~30V, the maintenance time of each segment is 1~3min, and the negative direction is not loaded. As a preferred solution, when the forward direction is in constant voltage mode, the forward voltage is 500-750V, the holding time is 5-50min, and the negative direction is not loaded. Further preferably, when the forward direction is in constant voltage mode, the forward voltage is 600-700V, the holding time is 10-20min, and the negative direction is not loaded.
[0015] As a preferred solution, when the forward direction is in constant current mode, the forward current is 1-5A, the negative current is 0.1-0.5A, and the maintenance time is 5-50min.
[0016] The micro-arc oxidation treatment provided by the present invention must be strictly performed in accordance with the above requirements, wherein the forward electrical control method is one of the key technical parameters of the present invention. When only the constant voltage mode is used, only when the voltage is higher than 500V, a uniform ceramic film layer can be formed on the surface of the material. As the voltage increases, the color of the film layer continues to deepen, and the thickness of the film layer continues to increase. However, the increase in film thickness is not unlimited. When the voltage is higher than 750V, the surface of the film layer will be ablated or fall off, and a complete coating cannot be formed. The advantage of the constant voltage mode is that a thicker ceramic film layer can be prepared in a short time. The stepped constant voltage plus constant current mode is an important way to further optimize the process parameters. By adopting this electrical control method, the porosity of the film layer can be further reduced on the basis of the constant voltage mode, and the hardness and corrosion resistance of the film layer surface can be improved.
[0017] As a preferred solution, during the micro-arc oxidation process, the temperature of the electrolyte is less than 50°C.
[0018] Based on the electrolyte system provided by the present invention, during the micro-arc oxidation process of steel as an anode, complex electrochemical reactions occur in the local high-energy field micro-region on its surface, thereby realizing the in-situ growth of ceramic coating. The process is mainly as follows: in the initial stage of the reaction, a loose, porous, brown-yellow film layer is first produced on the surface of the steel, and its main component is Fe2O3. As the voltage and current increase, under the action of the electrolyte, the film layer further reacts to form a dense layer of ferroferric oxide and aluminum oxide, thereby obtaining a ceramic coating.
[0019] As a preferred solution, the cleaning process of the steel after micro-arc oxidation is: the steel is rinsed with tap water and then ultrasonically cleaned with deionized water for 10 minutes.
[0020] The present invention also provides a ceramic coating grown in situ by micro-arc oxidation on the surface of steel, which is obtained by any of the methods described above; the main components of the ceramic coating are approximately: Fe3O4 40-45% and Al2O3 30-40%.
[0021] As a preferred solution, the thickness of the ceramic coating is 50-300 μm, and the hardness is 500-700 HV. More preferably, the thickness of the ceramic coating is 100-200 μm, and the hardness is 650-700 HV.
[0022] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are: 1) The ceramic coating provided by the present invention is based on the synergistic effect between the electrolyte system and the micro-arc oxidation treatment. While achieving the in-situ growth of a thicker film layer in a short time, it also greatly improves the comprehensive performance of the film layer. After testing, the ceramic coating provided by the present invention has a thickness of up to 131 μm, a hardness of up to 650 HV or more, and an ultra-low glossiness, with a maximum glossiness of only 0.1. The film layer also has excellent photocatalytic properties, and can reduce the concentration of methyl orange with a concentration of 5 mg / L by more than 80% in 12 hours, and can be used for catalytic oxidation and degradation of organic matter in an aquatic environment.
[0023] 2) The method provided by the present invention can not only greatly improve the growth rate of the ceramic coating, but also realize quantitative control of the thickness of the ceramic coating by controlling the electrical control parameters during the micro-arc oxidation treatment process. Since the method mainly utilizes the electrochemical reaction between the electrolyte and the local high-energy field micro-region on the surface of the steel to grow the ceramic coating, the method does not need to prepare a conversion layer on the surface of the substrate, and can realize the preparation of a ceramic coating with a thickness of more than 100 μm on the surface of medium-carbon steel and mold steel with a high carbon content in a short time. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an image of the ceramic coating prepared in Comparative Example 1 of the present invention; Figure 2 This is an image of the ceramic coating prepared in Comparative Example 2 of the present invention; Figure 3 This is an image of the ceramic coating prepared in Comparative Example 3 of the present invention; Figure 4 This is an image of a ceramic film with a thickness of 131 μm prepared in Example 1 of the present invention; Figure 5 This is an image of a ceramic film with a thickness of 98 μm prepared in Example 2 of the present invention; Figure 6 This is a SEM image of a ceramic film with a thickness of 131 μm prepared in Example 1 of the present invention; Figure 7 This is a cross-sectional morphology diagram of a ceramic film with a thickness of 131 μm prepared in Example 1 of the present invention; Figure 8 This is an XRD analysis diagram of a ceramic coating with a thickness of 131 μm and an H13 steel substrate material prepared in Example 1 of the present invention; Fig. 9 Friction curve of the ceramic coating with a thickness of 53 μm prepared in Example 7 of the present invention and the H13 steel substrate material; Fig.10 This is a wear scar profile diagram of the ceramic coating with a thickness of 53 μm and the H13 steel substrate material prepared in Example 7 of the present invention after dry sliding friction with a G-Cr15 steel ball under a load of 10N; Fig.11 This is a polarization curve diagram of a ceramic coating with a thickness of 131 μm and an H13 steel substrate material prepared in Example 1 of the present invention; Fig.12 The Vickers hardness indentation micromorphology of the ceramic coating with a thickness of 131 μm and the H13 steel substrate material prepared in Example 1 of the present invention; in, Fig.12 (ae) are five different indentation measurement points on the surface of the ceramic membrane. Fig.12 (f) is the Vickers hardness indentation microstructure of H13 steel substrate; Fig.13 A bar chart showing a comparative analysis of the Vickers hardness values of the ceramic coating with a thickness of 131 μm and the H13 steel substrate material prepared in Example 1 of the present invention; Fig.14 It is the absorbance change of methyl orange indicator during self-degradation within 48 hours; Fig.15 This is a color change diagram of the methyl orange indicator after the ceramic film with a thickness of 131 μm prepared in Example 1 of the present invention is treated with light for different time periods; Fig.16 The graph is a graph showing the concentration and absorbance variation of methyl orange for the ceramic film with a thickness of 131 μm prepared in Example 1 of the present invention after being exposed to light for different periods of time. DETAILED DESCRIPTION
[0025] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner in conjunction with the accompanying drawings and preferred embodiments of the specification. It should be noted that the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Comparative Example 1 This embodiment provides a method for in-situ growth of ceramic coating on the surface of steel by micro-arc oxidation, and the specific method is as follows: 1. Preparation of inorganic salt electrolyte Add NaSiO3 to high-purity deionized water, stir thoroughly until clear, cool to room temperature for use, then add NaH2PO4, stir thoroughly until clear, cool to room temperature for use, the concentration of NaSiO3 in the electrolyte is 8g / L, and the concentration of NaH2PO4 is 2g / L; 2. Workpiece pretreatment The H13 steel plate was cut into samples with the size of 20×15×5 mm, and polished with 80#, 320#, 600#, and 1000# SiC sandpaper respectively, and then ultrasonically cleaned and blown dry for later use; 3. Micro-arc oxidation treatment 1) Setting of electric control parameters: frequency 1000Hz, positive and negative pulse number ratio 1:0, positive duty cycle 5%, forward constant voltage mode, voltage set to 500V, maintained for 15min; 2) Use a stainless steel electrolytic cell as the cathode and a φ3mm titanium alloy rod as the tooling. Place the workpiece in the center of the electrolytic cell as the anode, add electrolyte, and perform micro-arc oxidation treatment. During the treatment, maintain the electrolyte temperature below 50°C through a circulating water cooling system.
[0027] 4. Workpiece post-processing The workpiece after micro-arc oxidation treatment was first rinsed with tap water, then ultrasonically cleaned with deionized water for 10 minutes, and then air-dried.
[0028] Comparative Example 2 This embodiment is exactly the same as Comparative Example 1, except that the concentration of NaSiO3 in the electrolyte is 8 g / L, the concentration of (NaPO3)6 is 2 g / L, and the forward voltage is set to 600V.
[0029] Comparative Example 3 This embodiment is exactly the same as Comparative Example 1, except that the concentration of NaAlO2 in the electrolyte is 8 g / L, the concentration of NaH2PO4 is 2 g / L, and the forward voltage is set to 600V.
[0030] Example 1 This embodiment provides a method for in-situ growth of ceramic coating on the surface of steel by micro-arc oxidation, and the specific method is as follows: 1. Preparation of inorganic salt electrolyte Add NaAlO2 to high-purity deionized water, stir thoroughly until clear, cool to room temperature for use, then add (NaPO3)6, stir thoroughly until clear, cool to room temperature for use, the concentration of NaAlO2 in the electrolyte is 8g / L, and the concentration of (NaPO3)6 is 2g / L; 2. Workpiece pretreatment The H13 steel plate was cut into samples with the size of 20×15×5 mm, and polished with 80#, 320#, 600#, and 1000# SiC sandpaper respectively, and then ultrasonically cleaned and blown dry for later use; 3. Micro-arc oxidation treatment 1) Setting of electric control parameters: frequency 1000Hz, positive and negative pulse number ratio 1:0, positive duty cycle 5%, positive adopts segmented constant voltage mode, that is, starting voltage 500V, holding time 2min, voltage 530V for 2min, voltage 560V for 2min, voltage 580V for 2min, voltage 600V for 2min, voltage 620V for 2min, voltage 650V for 2min, voltage 680V for 2min, no negative loading, and then switch to constant current control mode, that is, forward current 3.0A, negative current 0.1A, hold for 24min; 2) Use a stainless steel electrolytic cell as the cathode and a φ3mm titanium alloy rod as the tooling. Place the workpiece in the center of the electrolytic cell as the anode, add electrolyte, and perform micro-arc oxidation treatment. During the treatment, maintain the electrolyte temperature below 50°C through a circulating water cooling system.
[0031] 4. Workpiece post-processing The workpiece after micro-arc oxidation treatment was first rinsed with tap water, then ultrasonically cleaned with deionized water for 10 minutes, and then air-dried.
[0032] Example 2 This embodiment is exactly the same as the embodiment 1, except that the workpiece substrate is a 45 steel plate.
[0033] Example 3 This embodiment is exactly the same as the embodiment 1, except that the workpiece substrate is a Q235 steel plate.
[0034] Example 4 This embodiment is exactly the same as the embodiment 1, except that the workpiece substrate is a 316L stainless steel plate.
[0035] Example 5 This embodiment is completely the same as the embodiment 1, except that only the segmented constant voltage mode is adopted in the forward direction.
[0036] Example 6 This embodiment is completely the same as the embodiment 1, except that the forward direction is kept in the constant current control mode for 14 minutes after the segmented constant voltage mode.
[0037] Example 7 This embodiment is completely the same as the embodiment 1, except that only the constant voltage mode is used in the forward direction, the voltage is set to 680V and maintained for 15 minutes.
[0038] The thickness of the ceramic coatings obtained in Comparative Examples 1 to 3 and Examples 1 to 7 is shown in Table 1
[0039] Through Table 1 and Figures 1 to 5 It can be seen that the samples obtained in Comparative Examples 1 to 3 had ablation and falling off on the surface after only 15 minutes due to the replacement of the electrolyte components. However, the method provided by the present invention can form a ceramic coating not only on the surface of low-carbon steel, but also on the surface of medium-carbon steel and stainless steel with a thickness of more than 100 μm. Based on the synergistic effect between the electrolyte and micro-arc oxidation in the technical scheme of the present invention, a ceramic coating of about 50 μm can be formed on the surface of medium-carbon steel in about 15 minutes, which fully proves that the ceramic coating has excellent growth rate and uniformity under this method.
[0040] Furthermore, the present invention also carried out XRD test on the sample obtained in Comparative Example 1, and the results are as follows: Figure 8 As shown, through Figure 8 It can be seen that the main components of the ceramic film are Fe3O4 and Al2O3, and the peak of Fe atoms also appears in the film layer, which indicates that the main components of the ceramic film provided by the present invention come from the iron element in the steel matrix and the AlO2 in the solution. − , which indirectly proves that the growth process of the ceramic coating is in-situ growth.
[0041] In order to prove that the ceramic coating provided by the present invention has excellent wear resistance, the present invention also conducted a friction test on the ceramic coating of Example 7 and the H13 steel substrate material. The test results are as follows: Fig. 9 As shown, through Fig. 9 It can be seen that the friction coefficient of the ceramic coating is much lower than that of the H13 steel substrate. Under a load of 10N, the sample can continue to dry-slide with the G-Cr15 steel ball for 1800s, and the surface of the film is almost intact. Fig.10 From the comparison of the substrate and the wear scar profile, it can be seen that although the wear scar profile in the image shows sawtooth fluctuations, the reason for the fluctuations is that the debris of the steel ball is transferred to the surface of the film layer, and the high and low undulating structure is formed by continuous plastic deformation during the friction process.
[0042] The ceramic coating provided by the present invention also has excellent stability and hardness. The polarization curves of the samples before and after micro-arc oxidation treatment are as follows: Fig.11 As shown in the figure, it can be seen that the corrosion current density of the sample after micro-arc oxidation treatment is reduced by an order of magnitude, and the width of the passivation zone is significantly higher than that of the untreated H13 steel. Furthermore, the Vickers hardness indentation micromorphology of the H13 steel treated with micro-arc oxidation is shown in Fig.12 As shown by Fig.13 It can be seen that the maximum hardness of the film layer reaches 684.17 HV, which is much higher than the hardness of the substrate 186.02 HV.
[0043] Since the ceramic film provided by the present invention is mainly composed of Fe3O4 and doped with Al2O3, the film also has high photocatalytic activity. The present invention also conducted a photocatalytic degradation test of methyl orange solution: First, the self-degradation absorbance curve of methyl orange after 48 hours under light conditions is as follows: Fig.14 As shown in the figure, the absorbance of methyl orange reaches a peak at a wavelength of about 464 nm, which is used as the standard value of absorbance. After 48 hours of irradiation, the self-degradation degree of methyl orange is only 5%, which shows that the use of methyl orange as an indicator in this experiment is stable and reliable; then, the sample treated with micro-arc oxidation was placed in a 5 mg / L methyl orange solution. Under the irradiation of an ultraviolet xenon lamp, the color changes of the methyl orange solution after different times are shown in the figure. Fig.15 The concentration and absorbance changes after different irradiation times are shown in Fig.16 As shown, from Fig.15 It can be seen that the color of the methyl orange solution becomes lighter with time, and is basically clear and transparent at 12 hours. Fig.16 It can be clearly determined that the degradation degrees of methyl orange after 2h, 6h, 8h and 12h were 28.26%, 56.47%, 63.52% and 81.49% respectively, which further proves that the ceramic coating has excellent photocatalytic properties.
[0044] From the above description, it can be seen that the ceramic coating generated in situ by the electrolyte + micro-arc oxidation treatment of the present invention can significantly improve the corrosion resistance, hardness and photocatalytic degradation performance of steel materials. The ultra-low glossiness also makes the coating have great application prospects in the fields of decoration and optics, and the technical solution provided by the present invention can be applied to the surface ceramic treatment of various steel substrate materials and realize quantitative control of the coating thickness.
Claims
1. A method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation, characterized in that: include: Step S1, the steel is placed as an anode in an electrolytic cell after being pretreated; Step S2, adding an electrolyte containing sodium aluminate and sodium hexametaphosphate into an electrolytic cell, using the electrolytic cell as a cathode, and performing micro-arc oxidation treatment on the steel; Step S3, cleaning and drying the steel material after micro-arc oxidation, to obtain; The concentration of sodium aluminate in the electrolyte is 7-9 g / L, and the concentration of sodium hexametaphosphate is 1-3 g / L.
2. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 1, characterized in that: The pretreatment process of the steel material is: after cutting the steel material, grinding, polishing and ultrasonic cleaning are used to remove surface stains and oxide layers.
3. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 1, characterized in that: The electrolyte also contains an auxiliary additive with a concentration of 0-50 g / L; the auxiliary additive is at least one of silicate, vanadate, tungstate, alkali, rare earth element, coordination salt of colored ions, metal oxide and polymer particles.
4. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 1, characterized in that: The electrical control parameters of the micro-arc oxidation treatment are: the positive voltage is 200~750V, the negative voltage is 0~250V, and the current density is 5~50A / dm 2 , frequency is 50~10000Hz, and duty cycle is 5~95%.
5. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 4, characterized in that: The positive direction adopts at least one of a segmented constant voltage mode, a constant voltage mode and a constant current mode; the negative direction adopts a constant voltage mode or a constant current mode, and the average current intensity in the negative direction is less than or equal to the average current intensity in the forward direction.
6. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 5, characterized in that: When the forward direction adopts the segmented constant voltage mode, the starting voltage is 200-500V, the number of segments is 5-10, the voltage increment of each segment is 10-50V, the holding time of each segment is 1-5min, and there is no loading in the negative direction.
7. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 5, characterized in that: When the forward direction is in constant voltage mode, the forward voltage is 500-750V, the maintenance time is 5-50min, and the negative direction is not loaded; when the forward direction is in constant current mode, the forward current is 1-5A, the negative current is 0.1-0.5A, and the maintenance time is 5-50min.
8. The method for in-situ growth of ceramic coating on steel surface by micro-arc oxidation according to claim 1, characterized in that: During the micro-arc oxidation treatment process, the temperature of the electrolyte is less than 50° C. The cleaning process of the steel after micro-arc oxidation is: the steel is rinsed with tap water and then ultrasonically cleaned with deionized water for 10 minutes.
9. A ceramic coating grown in situ by micro-arc oxidation on the surface of steel, characterized in that: Obtained by the method described in any one of claims 1 to 8; the main components of the ceramic coating are: Fe3O4 40-45% and Al2O3 30-40%.
10. The ceramic coating grown in situ by micro-arc oxidation on the surface of steel according to claim 9, characterized in that: The ceramic coating has a thickness of 50-300 μm and a hardness of 500-700 HV.